INTEGRASI GEOGEBRA DAN JOYFUL LEARNING SEBAGAI STRATEGI EFEKTIF UNTUK MENINGKATKAN LITERASI MATEMATIS SISWA - Habibah, Nur; Aminah, Neneng; Shafinaz, Shafinaz (Prodi Pendidikan Matematika FKIP Universitas Madura, 2025)
Mathematics is a subject that is often associated with logic and good mathematical skills, one of which is mathematical literacy. Mathematical literacy ability is the ability to understand mathematical concepts, represent mathematical models. The indicators of this research refer to the theory put forward by Garner, namely the Multiple Intelligences theory, including aspects of logical-mathematical, musical, and intrapersonal intelligence, which can affect how to understand and solve mathematical problems. This research was conducted at MA NU Assalafie in Cirebon Regency with a sample of 40 students divided into 5 groups, with one group having 8 students. This study uses the Geogebra application with a joyful learning approach. The t-test result was 0.049 with a sig value < 0.05. This research uses the Geogebra application as an innovative learning medium. The development of increasingly advanced technology makes this mathematical science can be combined with the use of application-based technology.